The doctrines and transformation of the Huang-Lao tradition - Chen, L. K. (Springer, Dordrecht, 2020)
This chapter provides an introduction to the Huang-Lao tradition. While the Huang-Lao tradition is conventionally regarded as a branch of Daoism, scholarly opinions diverge even on what the referent of the term “Huang-Lao” is. This chapter attempts to show that the issue of classifying the Huang-Lao tradition is indeed a controversial and intricate one in scholarship. Taking into account major scholarly debates, the discussion in this chapter is divided into three main sections. The first section provides a historical account of the origin and development of the Huang-Lao tradition. The second section discusses the important texts wherein sources of Huang-Lao thought are found and, in doing so, sheds light on the linkages between the Huang-Lao and other traditions or texts. Against the background of these intellectual linkages, the third section surveys the key concepts in Huang-Lao thought: wuwei (inaction), fa (law), xing ming (forms and names), Dao, shu (technique), and personal cultivation.